2019
DOI: 10.1080/08927014.2018.1563686
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm inhibition and anti-quorum sensing activity of phytosynthesized silver nanoparticles against the nosocomial pathogen Pseudomonas aeruginosa

Abstract: Quorum sensing (QS), the communication signaling network, regulates biofilm formation and several virulence factors in Pseudomonas aeruginosa PAO1, a nosocomial opportunistic pathogen. QS is considered to be a challenging target for compounds antagonistic to virulent factors. Biologically synthesized silver nanoparticles (AgNPs) are reported as anti-QS and anti-biofilm drugs against bacterial infections. The present study reports on the synthesis and characterization of Piper betle (Pb) mediated AgNPs (Pb-AgNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 86 publications
9
66
0
Order By: Relevance
“…To date, it has been shown that AuNPs and AgNPs, along with their respective ions, interact with several structural proteins, membrane proteins and several enzymes [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In an experimental and molecular docking study, Shah et al evidenced the diverse action of AgNPs on various proteins of Pseudomonas aeruginosa [ 32 ]. First, they showed a reduction in the amount of elastase, a QS-mediated virulence factor, caused even by exposure to sublethal doses of AgNPs.…”
Section: Interaction Of Gold and Silver Nanoparticles With Biofilmmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, it has been shown that AuNPs and AgNPs, along with their respective ions, interact with several structural proteins, membrane proteins and several enzymes [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In an experimental and molecular docking study, Shah et al evidenced the diverse action of AgNPs on various proteins of Pseudomonas aeruginosa [ 32 ]. First, they showed a reduction in the amount of elastase, a QS-mediated virulence factor, caused even by exposure to sublethal doses of AgNPs.…”
Section: Interaction Of Gold and Silver Nanoparticles With Biofilmmentioning
confidence: 99%
“…For MvfR protein, the docking showed only hydrophobic interactions and hydrogen-bonding interactions at the active site. Their overall experimental results gave proof of QS inhibition and biofilm destruction [ 32 ]. In a similar study, with homology modeling, Vyshnava et al showed interactions of four proteins involved in the signal transduction system of P. aeruginosa (LasR, QscR, RhlR and Vfr) with AgNPs, which resulted in their binding and inhibition [ 33 ].…”
Section: Interaction Of Gold and Silver Nanoparticles With Biofilmmentioning
confidence: 99%
“…Biofilm is a cell function whose gene expression is regulated by quorum sensing [17,18]. Therefore, quorum quenching mechanisms which is interfering quorum sensing mechanisms might be a good alternative to overcome biofilm problems [19]. Based on quantification of biofilm activity both in inhibition and destruction steps (Table 2), these extracts showed various results.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm is a cell function whose gene expression is regulated by quorum sensing [17,18]. Therefore, quorum quenching mechanisms might be a good alternative to overcome biofilm problems [19].…”
Section: Discussionmentioning
confidence: 99%